2023
DOI: 10.33689/spormetre.1187404
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Secondary School Students' Sportsmanship Behaviors in Physical Education and Sports Lesson

Abstract: In this study, it was aimed to examine the sportsmanship behaviors of secondary school students in physical education and sports lessons. The sample of the study consists of 949 students selected by simple random sampling, continuing their education in Hatay in the 2021-2022 academic year. “Physical Education Lesson Sportsmanship Behavior Scale” was used as a data collection tool in the research. Descriptive statistics, t, and ANOVA tests were performed in the analysis of the data. According to the research fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
0
0
Order By: Relevance
“…In another study, it was determined that students' sportsmanship behaviors were at a better level than their negative behaviors. While displaying sportsmanship behaviors does not differ according to gender, it is observed that students' ability to avoid negative behaviors decreases as their grade levels increase (Temel et al, 2023). Federation, the organization of the Federation as the School Sports Department affiliated to the General Directorate of Sports Services in 2023, and the presence of sports halls in newly built schools.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In another study, it was determined that students' sportsmanship behaviors were at a better level than their negative behaviors. While displaying sportsmanship behaviors does not differ according to gender, it is observed that students' ability to avoid negative behaviors decreases as their grade levels increase (Temel et al, 2023). Federation, the organization of the Federation as the School Sports Department affiliated to the General Directorate of Sports Services in 2023, and the presence of sports halls in newly built schools.…”
Section: Conclusion and Discussionmentioning
confidence: 99%